The Bending Responses of Sandwich Panels with Aluminium Honeycomb Core and CFRP Skins Used in Electric Vehicle Body. (7th August 2018) - Xiao, Yong; Hu, Yefa; Zhang, Jinguang; Song, Chunsheng; Huang, Xiangyang; Yu, Jingui; Liu, Zhaobing
Abstract : The aim of this paper was to investigate bending responses of sandwich panels with aluminium honeycomb core and carbon fibre-reinforced plastic (CFRP) skins used in electric vehicle body subjected to quasistatic bending. The typical load-displacement curves, failure modes, and energy absorption are studied. The effects of fibre direction, stacking sequence, layer thickness, and loading velocity on the crashworthiness characteristics are discussed. The finite element analysis (FEA) results are compared with experimental measurements. It is observed that there are good agreements between the FEA and experimental results. Numerical simulations and experiment predict that the honeycomb sandwich panels with ±30° and ±45° fibre direction, asymmetrical stacking sequence (45°/−45°/45°/−45°), thicker panels (0.2 mm∼0.4 mm), and smaller loading velocity (5 mm/min∼30 mm/min) have better crashworthiness performance. The FEA prediction is also helpful in understanding the initiation and propagation of cracks within the honeycomb sandwich panels.